2017
DOI: 10.3389/fphar.2017.00915
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine Dithiocarbamate (PDTC) Attenuates Cancer Cachexia by Affecting Muscle Atrophy and Fat Lipolysis

Abstract: Cancer cachexia is a kind of whole body metabolic disorder syndrome accompanied with severe wasting of muscle and adipose tissue. NF-κB signaling plays an important role during skeletal muscle atrophy and fat lipolysis. As an inhibitor of NF-κB signaling, Pyrrolidine dithiocarbamate (PDTC) was reported to relieve cancer cachexia; however, its mechanism remains largely unknown. In our study, we showed that PDTC attenuated cancer cachexia symptom in C26 tumor bearing mice models in vivo without influencing tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…Inflammatory mediators [tumor necrosis factor-α (TNF-α), interleukin-1 and interleukin -6] are key contributors to the development of cancer cachexia, which is the driving forces of skeletal muscle atrophy caused by cancer cachexia (6,7). TNF-α was often used to induce a model of muscle atrophy in cancer cachexia (8)(9)(10). Therefore, to elucidate the molecular mechanism and develop targeted therapies of cachexia associated muscle atrophy is of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory mediators [tumor necrosis factor-α (TNF-α), interleukin-1 and interleukin -6] are key contributors to the development of cancer cachexia, which is the driving forces of skeletal muscle atrophy caused by cancer cachexia (6,7). TNF-α was often used to induce a model of muscle atrophy in cancer cachexia (8)(9)(10). Therefore, to elucidate the molecular mechanism and develop targeted therapies of cachexia associated muscle atrophy is of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, up to now, there is no approved therapeutic agent for the treatment or prevention of cancer cachexia. 17 Results of the present study showed that SBCC treatment could partly ameliorate cachexia symptoms of mice bearing C26 tumor. SBCC signicantly ameliorates the decrease in body temperature in cachexia mice and slightly ameliorates the decrease in body weight.…”
Section: Discussionmentioning
confidence: 49%
“…Cancer cachexia in mice was induced as reported in our previous report. 17 Briey, a total of 24 male BALB/c mice (6-8 weeks old) were randomly divided into three groups (8 mice per group): healthy group without tumor (Health group), C26 tumor-bearing mice group (C26 model group) and C26 tumorbearing mice treated with SBCC (1.5 g kg À1 ) group (C26 + SBCC group). On day 0, mice received subcutaneous injections of C26 tumor cells (1.0 Â 10 6 cells/0.1 ml) in the right ank.…”
Section: Cancer Cachexia Mice Modelmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 In addition, the production of lipid-metabolising factor induces consequent lipolysis that results in patients’ progressive weight loss. 8 Pro-inflammatory cytokines contribute to the pathophysiology of neoplastic cachexia, such as interleukins 1 and 6, tumor necrosis factor alpha, and interferon gamma, which in turn results in an increase in C-reactive protein (CRP), haptoglobin and ceruloplasmin that are responsible for increased fatty acid turnover and muscle proteolysis. 9 Neoplastic cachexia is frequently associated with anorexia due to qualitative and quantitative alterations in hypothalamic signals, including the inhibition of the orexigenic effect of neuropeptide Y, induced by pro-inflammatory cytokines, and the increase in corticotropin-releasing factor and melanocortin.…”
Section: Introductionmentioning
confidence: 99%